Jane Mink Rossen - Uri Sharvit. A Fusion of Traditions: Liturgical Music in the Copenhagen Synagogue.: Odense: University Press of Southern Denmark, 2006, 156 pp + 1 accompanying CD, ISBN 87-7674-038-2. - Seidlová, Veronika (Lidé města, 2007)
A review of the book by Jane Mink Rossen and Uri Sharvit.